Potentiality of producing summer cauliflower as influenced by organic manures and spacing (Asian Journal of Medical and Biological Research, 2016)
The experiment was conducted to find out the effect of organic manures and spacing on the growth and yield of cauliflower in summer season. In this study, the treatment consisted of three organic manures viz. F0: no organic manure, F1: cowdung, F2: vermicompost and three spacing viz. S1 (60 × 30) cm, S2 (60 × 40) cm, S3 (60 × 50) cm. Two factorial experiments were laid out in the RCBD with three replications. Significant variations in all parameter were observed due to organic manure and spacing at different days after transplanting. For organic manure, highest yield of cauliflower (12.98 t ha-1) was obtained from F2 and lowest (8.24 t ha-1) from F0. For spacing, highest yield of cauliflower (11.25 t ha-1) was obtained from S1 and lowest (10.57 t ha-1) from S3. For combined effect, highest yield of cauliflower (13.33 t ha-1) was obtained from F2S1 and the lowest (7.91 t ha-1) from F0S3. The highest BCR (3.79) was found from F2S1 and lowest (2.7) from F0S3. It is found from the experiment that growth and yield of summer cauliflower were positively correlated with organic manure and spacing. However, white beauty cultivars can be cultivated in summer season and use of vermicompost with 60×50 cm spacing would be beneficial for the farmers.Asian J. Med. Biol. Res. June 2016, 2(2): 304-317